Influence of amount and frequency of protein supplementation to ruminants consuming low-quality cool-season forages: efficiency of nitrogen utilization in lambs and performance of gestating beef cows. (19th April 2021) - Cappellozza, Bruno I; Bohnert, David W; Reis, Maria M; Van Emon, Megan L; Schauer, Christopher S; Falck, Stephanie J; Cooke, Reinaldo F
Abstract: We evaluated the influence of amount and crude protein (CP ) supplementation frequency (SF ) on nitrogen (N) use by wethers and the performance of late-gestation beef cows. In exp. 1, seven Western whiteface wethers (31.8 ± 1.4 kg) were used in an incomplete 7 × 4 Latin square to evaluate intake and N use. Wethers received one of the seven treatments in a 2 × 3 factorial design containing two levels of supplemental soybean meal offered at a rate of 100% (F ) or 50% (H ; 50% of F) of the estimated CP requirement daily, once every 5, or once every 10 d, plus a non-supplemented control (CON ). Low-quality cool-season forage (4.9 % CP; dry matter [DM ] basis) was provided daily for ad libitum intake. Experimental periods lasted 30 d. In exp. 2, 84 Angus × Hereford cows (560 ± 35 kg) were stratified by age, body condition score (BCS ), and expected calving date and allocated to 1 of the 21 feedlot pens (three pens per treatment). Pens were randomly assigned to receive the same treatments as in exp. 1 and cows had free access to low-quality cool-season forage (2.9% CP; DM basis). Cow body weight (BW ) and BCS were measured every 14 d until calving and within 24 h after calving. In exp. 1, supplementation did not alter total DM and organic matter (OM ) intake ( P ≥ 0.26), but both parameters linearly decreased as SF decreased ( P = 0.02). Supplementation increased DM, OM, and neutral detergent fiber (NDF ) digestibility ( P ≤ 0.02). Additionally, F feeding linearly increased DM, OM, and NDF digestibility as SF decreased ( P ≤ 0.04). Digestibility of N, N balance, and digested N retained were greater with supplementation ( P < 0.01), and N digestibility linearly increased as SF decreased ( P = 0.01). Mean plasma urea-N concentration was not only greater ( P < 0.01) for supplemented vs. CON wethers but also greater ( P = 0.03) for F vs. H. In exp. 2, pre-calving BCS change was greater ( P = 0.03) for supplemented cows. A linear effect of SF × supplementation rate for pre-calving BCS change was noted ( P = 0.05), as F-supplemented cows lost more BCS compared with H as SF decreased. When considering supplementation intervals greater than 5 d, reducing the quantity of supplement provided, compared with daily supplementation, may be a feasible management strategy to maintain acceptable nutrient use and animal performance while reducing supplement and labor costs.